Revealing the underlying mechanisms of nanoplastics induces neuroinflammation: From transcriptomic analysis to in vivo and in vitro validation - Xiaomei Lu; Qinghua Luo; Jiahao Zhao; Ming Li; Dandan Liu (Ecotoxicology and Environmental Safety)
With the widespread use of plastic products globally, the harmful impacts of nanoplastics (NPs) on human health are not to be underestimated. Although the NPs-induced neurotoxicity has already been affirmed, the related mechanisms are still not fully understood. Therefore, this study aims to reveal the underlying mechanisms of NPs-induced neurotoxicity. After mice were randomly divided into the control, low-dose polystyrene nanoplastics (PS-NPs-L, 10 mg/kg), middle-dose PS-NPs (PS-NPs-M, 20 mg/kg), and high-dose PS-NPs (PS-NPs-H, 50 mg/kg) groups, we discovered PS-NPs with a mean diameter of approximately 100 nm were accumulated in the brain of mice, induced anxiety-like behaviors and cognitive dysfunction, caused pathological injuries to the mice’s prefrontal cortex tissue, and elevated the Iba1 and GFAP expression in the mice’s prefrontal cortex tissue. After BV-2 cells were randomly divided into the control, PS-NPs-L (25 μg/mL), PS-NPs-M (50 μg/mL), and PS-NPs-H (75 μg/mL) groups, we discovered PS-NPs inhibited cell viability, arrested the cell cycle in the G2 phase, and enhanced apoptosis and the ROS level of BV-2 cells. The transcriptomic analysis based on mice’s prefrontal cortex tissues screened four shared DEGs, namely Pbx3, Ecell, Crb1, and Ngb. The differentially expressed genes were enriched in multiple pathways, especially the positive regulation of NIK/NF-kappaB signaling. In vitro, PS-NPs also increased the mean fluorescence intensity of p65, TNF-α, and IL-1β of BV-2 cells. In vivo and in vitro, PS-NPs up-regulated the mRNA and protein expression levels of NF-κB, TNF-α, and IL-1β. Our studies affirmed that PS-NPs induced neuroinflammation by activating the NF-κB signaling to promote the release of TNF-α and IL-1β based on transcriptomic analysis as well as in vivo and in vitro validation.